2020
DOI: 10.1111/hex.13095
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy experiences of multi‐ethnic patients and their health‐care providers in the management of type 2 diabetes in Malaysia: A qualitative study

Abstract: Background Patients with type 2 diabetes mellitus (T2DM) require adequate health literacy to understand the disease and learn self‐management skills to optimize their health. However, the prevalence of limited health literacy is high in patients with T2DM, especially in Asian countries. Objective This study aimed to explore experiences related to health literacy in Asian patients with T2DM. Design This is a qualitative study using in‐depth interviews and focus group discussions. A framework analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…Compared with all of these countries, the prevalence of limited HL was the lowest in our study. One of the reasons for this could be that our population involved patients who had chronic diseases and would have had regular access to health-care services provided by clinicians who are skilled in their field [20,44,45]. All of the doctors at this clinic were either family medicine specialists or postgraduate doctors pursuing a Master's degree in family medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with all of these countries, the prevalence of limited HL was the lowest in our study. One of the reasons for this could be that our population involved patients who had chronic diseases and would have had regular access to health-care services provided by clinicians who are skilled in their field [20,44,45]. All of the doctors at this clinic were either family medicine specialists or postgraduate doctors pursuing a Master's degree in family medicine.…”
Section: Discussionmentioning
confidence: 99%
“…All of the doctors at this clinic were either family medicine specialists or postgraduate doctors pursuing a Master's degree in family medicine. The ongoing clinical training and continuous professional development activities they undergo may have an effect on these patients' HL levels [20,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…This factor (9 items) was dispersed into Understanding and Managing my CKD (originally known as Self-integration) (5 items) and Seeking Support (originally Seeking Social Support) (4 items). This is related to the local family dynamic where no individual (health) problem should be kept from the family [31,32]. Problem-solving in health problems is a family issue, and begins in personal understanding of the problem at hands.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative studies exploring health literacy in diabetes in Asian cultures found that culture shaped understanding and experiences of health literacy. [10, 11, 12]. There are significant ethnic differences in how physical health conditions are recognised and labelled.…”
Section: Introductionmentioning
confidence: 99%